2014
DOI: 10.1186/s12935-014-0128-2
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of microRNA-196a and microRNA-196b cooperatively correlate with aggressive progression and unfavorable prognosis in patients with colorectal cancer

Abstract: BackgroundBoth microRNA (miR)-196a and miR-196b are implicated in normal cell differentiation, proliferation, and in tumorigenesis of various cancer types. Especially, miR-196a exerts a pro-oncogenic influence in colorectal cancer (CRC) cells and miR-196b expression is upregulated in CRC tissues. The aim of this study was to evaluate the associations of miR-196a and miR-196b dysregulation with clinicopathological characteristics and prognosis in patients with CRC.MethodsQuantitative real time-PCR (qRT-PCR) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 30 publications
(29 reference statements)
5
44
0
1
Order By: Relevance
“…As the molecules of miRNAs are small and relatively easy to be secreted into extracellular microenvironments and devoured by nearby cells, the secreted miRNAs function to regulate cancer cell proliferation, migration, intercellular communication, and stromal modification, thereby helping the cancer cells to establish their microenvironments for metastasis [82]. These results are consistent with previous studies reporting that upregulation of miR-196a was found to be correlated with advanced tumor stage and poor overall and recurrence-free survival in many cancer patients [8,52]. This upregulation could suppress annexin A1; an inhibitor of cell proliferation, and mediator of apoptosis and anchorage-independent growth [68], enhance G1/S-phase transition and the proliferative ability of cancer cells through targeting FOXO1 and p27Kip1; two key effectors of the PI3K/Akt signaling pathway that regulates cell proliferation and has been addressed as a therapeutic target [8,9], up-regulate the ubiquitin-conjugating enzyme E2C (UBE2C) proto-oncogene [83], inhibit Bach1 (a basic leucine zipper mammalian transcriptional repressor) and upregulate hemeoxygenase 1 in HCV-related HCC [84], inhibit IjBa, which binds and tethers NF-jB in the cytoplasm; leading to translocation of the later into the nucleus where it activates a variety of target genes such as apoptosis-related genes Bax and Bcl-2 that regulate activation of caspase-3 [65], and regulates the Wnt-Fgf-Notch signaling pathways [85] that are commonly associated with tissue invasion and metastasis [86].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As the molecules of miRNAs are small and relatively easy to be secreted into extracellular microenvironments and devoured by nearby cells, the secreted miRNAs function to regulate cancer cell proliferation, migration, intercellular communication, and stromal modification, thereby helping the cancer cells to establish their microenvironments for metastasis [82]. These results are consistent with previous studies reporting that upregulation of miR-196a was found to be correlated with advanced tumor stage and poor overall and recurrence-free survival in many cancer patients [8,52]. This upregulation could suppress annexin A1; an inhibitor of cell proliferation, and mediator of apoptosis and anchorage-independent growth [68], enhance G1/S-phase transition and the proliferative ability of cancer cells through targeting FOXO1 and p27Kip1; two key effectors of the PI3K/Akt signaling pathway that regulates cell proliferation and has been addressed as a therapeutic target [8,9], up-regulate the ubiquitin-conjugating enzyme E2C (UBE2C) proto-oncogene [83], inhibit Bach1 (a basic leucine zipper mammalian transcriptional repressor) and upregulate hemeoxygenase 1 in HCV-related HCC [84], inhibit IjBa, which binds and tethers NF-jB in the cytoplasm; leading to translocation of the later into the nucleus where it activates a variety of target genes such as apoptosis-related genes Bax and Bcl-2 that regulate activation of caspase-3 [65], and regulates the Wnt-Fgf-Notch signaling pathways [85] that are commonly associated with tissue invasion and metastasis [86].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are mostly, but not always consistent with previous studies showing increased expression of miR-196a2 in several solid tumors [7], including esophageal adenocarcinoma [46], gastric cancer [9,[47][48][49], colorectal cancer [50][51][52], pancreatic cancer [53][54][55], hepatocellular carcinoma [56], breast cancer [57][58][59], cervical cancer [8,60], ovarian cancer [61], lung cancer [57,62,63], bone cancer [12,64], and malignant glioblastoma [22,65]. In contrast, miR-196a2 expression was reported to be down-regulated in prostate cancer cell lines [57] and melanoma cell lines [66] or tissues [67].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…miR-483-3p has been also associated with the capacity of adipocytes to store lipids and dysregulation of its expression could directly inhibit adipose tissue expandability and lipid storage, which in turn affect other tissues by stimulating ectopic triglyceride storage and lipotoxicity [36]. Regarding the other miRNAs and their function, miR-196b has been associated with inflammatory bowel disease [37], insulin [38] and cancer [39]; miR-346 has been implicated in rheumatoid arthritis [40], osteogenic differentiation [41] and cancer [42]; miR-1247 was implicated in cancer [43,44]; miR135a was implicated in proliferation [45], inflammation [46] and calcification [47]; and miR-193a-5p was associated with cancer [48,49]. Although their effects in the intestine need to be evaluated, it is clear that HT could specifically modulate their expression and exert biological effects through this mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…Emerging evidence has indicated that the aberrant expression of miR-196b is closely associated with leukemogenesis via increasing the population of leukemic stem/progenitor cells, blocking cell differentiation, promoting cell proliferation and diminishing cell apoptosis (19). Furthermore, Ge et al (20) demonstrated that expression of miR-196b in tissues may have a significant correlation with an aggressive progression of the disease and poor clinical outcomes in patients with CRC. However, the association between serum expression of miR-196b and CRC has yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%